Analytical Solution for Predicting Salt Precipitation During CO2 Injection Into Saline Aquifers in Presence of Capillary Pressure. Issue 6 (31st May 2022) - Norouzi, A. M.; Niasar, V.; Gluyas, J. G.; Babaei, M.
Abstract: Salt precipitation within pores of the reservoir is an important phenomenon occurring during CO2 injection into saline aquifers. The phenomenon results in permeability reduction and injectivity impairment. Salt precipitation mainly happens because of water vaporization inside the CO2 ‐saturated (dry‐out) region. For water‐wet systems, the capillary pressure acts toward the lower water saturation regions in the reservoir, thereby displacing a film of brine backward to the dry‐out region. This results in more precipitation. Overlooking this phenomenon, referred to as capillary‐driven backflow, results in over‐estimations of injectivity in the dried region. Here, we have developed an analytical solution based on fractional flow theory and shock waves for CO2 ‐brine systems considering the effect of capillary pressure. The validity of the solution is verified by comparing the outputs of our model with those of numerical results from a commercial numerical simulator for a hypothetical reservoir. An equation is derived to calculate the distance at which capillary pressure is most influential, and also the injectivity impairment at injection well due to salt precipitation was reasonably accurately estimated. The results emphasize that effects of capillary pressure should not be ignored. Key Points: Effects of capillary pressure were included in an analytical solution of CO2 injection into saline aquifers Capillary backflow induced salt precipitation affects injectivity of the wells in the aquifer The area that is mostly affected by salt precipitation, near the injection, can be estimated through mass balance